2020
DOI: 10.14245/ns.2040466.233
|View full text |Cite
|
Sign up to set email alerts
|

Three-Column Osteotomy for the Treatment of Rigid Cervical Deformity

Abstract: Adult cervical deformity (ACD) has been shown to have a substantial impact on quality of life and overall health, with moderate to severe deformities resulting in significant disability and dysfunction. Fortunately, surgical management and correction of cervical sagittal imbalance can offer significant benefits and improvement in pain and disability. ACD is a heterogenous disease and specific surgical correction strategies should reflect deformity type (driver of deformity) and patient-related factors. Spinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
(154 reference statements)
0
7
0
Order By: Relevance
“…1,9 The question of when cervical sagittal realignment procedures are needed is important because CSD procedures are typically more extensive than procedures for degenerative cervical pathology, require fusion of a greater number of motion segments, more often involve combined anterior and posterior approaches, more commonly require osteotomies, and have a higher rate of complications. [10][11][12][13][14][15] On the other hand, while operations to simply treat radiculopathy and/or myelopathy are often less invasive than CSD procedures, they may potentially have the risk of undertreating the problem and not addressing all potential pain generators or dynamic neurologic compression. In this study, we found that no single radiographic or clinical criteria by itself was sufficient to establish a diagnosis of CSD.…”
Section: Discussionmentioning
confidence: 99%
“…1,9 The question of when cervical sagittal realignment procedures are needed is important because CSD procedures are typically more extensive than procedures for degenerative cervical pathology, require fusion of a greater number of motion segments, more often involve combined anterior and posterior approaches, more commonly require osteotomies, and have a higher rate of complications. [10][11][12][13][14][15] On the other hand, while operations to simply treat radiculopathy and/or myelopathy are often less invasive than CSD procedures, they may potentially have the risk of undertreating the problem and not addressing all potential pain generators or dynamic neurologic compression. In this study, we found that no single radiographic or clinical criteria by itself was sufficient to establish a diagnosis of CSD.…”
Section: Discussionmentioning
confidence: 99%
“…This result was likely because among patients with CP, surgical invasiveness, need for surgical release, and utilization of osteotomies significantly increased in those with fixed cervical kyphosis than in those with semi-rigid or flexible kyphosis. In patients with CP, fixed cervical kyphosis is often accompanied by severe degenerative changes; thus, surgical treatment of such patients is challenging and requires invasive surgery to correct and stabilize the deformity while decompressing neural elements and restoring sagittal alignment [ 11 , 13 , 15 ]. Hence, patients with CSM and CP tend to undergo staged operations or combined approaches.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36] Subsequent literature has also demonstrated the clinical importance of stratifying deformities by rigidity, achieving global sagittal balance with regional alignment, and correcting of cervical alignment in extension. 32,37,38 system for patients with CSD. This followed similar attempts to unify nomenclature for cervical spine osteotomies and soft tissue releases.…”
Section: Modern Classification 1 Ames Classificationmentioning
confidence: 99%
“…Since the publication of the Ames criteria, several validations studies have demonstrated the correlation between advanced Ames deformity modifiers and progressive deformity [ 33 - 36 ]. Subsequent literature has also demonstrated the clinical importance of stratifying deformities by rigidity, achieving global sagittal balance with regional alignment, and correcting of cervical alignment in extension [ 32 , 37 , 38 ].…”
Section: Modern Classificationmentioning
confidence: 99%